Impact of innovation on performance of shipping companies in Singapore - Nah, Laura Yan Ling (2009)
Singapore’s maritime industry contributes approximately 7% of her GDP and employs over 100,000 people in more than 5,000 different establishments from various sectors of the industry. Before the recent economy downturn, the industry was expected to expand further by more than 5%. Now, it is even more important to ensure that the various sectors within the Singapore maritime industry continue to improve consistently. Innovation is one way to keep the maritime industry ahead, hence it is important to determine what influences innovation within the maritime industry and how innovation can improve company performances, in order to persuade firms to innovate. This report will focus on the four innovation types and their relationships with Singapore-registered ship-owning companies. The four innovation types that are used throughout the report are: (1) Product innovation; (2) Process innovation; (3) Marketing innovation; (4) Organizational innovation. A survey with 17 Singapore-registered ship-owning companies was conducted and results were checked for validity using the Spearman’s rho and Cronbach’s alpha tests. With the valid and reliable data, the results were analysed. Results showed that Singapore-registered ship-owning companies are considered innovative. The companies would also tend to focus on more than one type of innovation based on the costs of implementation. Marketing innovation was found to be the most popular while Organisational innovation was least popular.